ADMINISTRATION OF TOPICAL CORTICOSTEROIDS IN STANDARD SCHEME OF ATOPIC DERMATITIS IN CHILDREN - A.A. Alexeeva; Yu.G. Levina; E.A. Vishneva; S.K. Arshba ("Paediatrician" Publishers LLC, 2009)
The article presents the data on morphological and functional peculiarities of children's skin and on the administration of topical corticosteroids in children with allergodermatosis. An experience of administration of mometasone furoate, its advantages in treatment of children with atopic dermatitis is characterized. Key words: children, atopic dermatitis, topical corticosteroids, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):146-150)